Revamping Village Governance based on Insights from Law 6/2014 in Indonesia: Pembenahan Tata Kelola Desa berdasarkan Wawasan UU No. 6 Tahun 2014 di Indonesia - Anggraeni, Ditya Gita; UB, Ahmad Riyadh (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the implementation of Law Number 6 of 2014 in Gempol Village, Pasuruan Regency, focusing on factors hindering and supporting village officials' performance in orderly village administration. Using a descriptive qualitative approach with interviews, observation, and documentation, the research reveals challenges in communication, resource management, bureaucratic structure, and organizational culture among officials. Findings indicate a need for improved communication, resource allocation, and organizational culture to enhance Law Number 6 of 2014's effectiveness and overall village administration performance. Highlights: Communication gaps hinder Law 6/2014's effectiveness in Gempol Village. Resource allocation issues impact orderly administration in Gempol Village. Cultural change needed for better Law 6/2014 implementation in Gempol. Keywords: Implementation, Law Number 6 of 2014, Gempol Village, Performance, Orderly Administration